ANALISIS FAKTOR-FAKTOR YANG MENDORONG PERUSAHAAN MEREVALUASI ASET TETAP - Nidza Annisa Aziz; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2017)
The inflation volatility in Indonesia demands corporations to choose an accounting policy in order to count the actual rate of the fixed assets. Fixed asset revaluation is a review of a corporate’s fixed asset. The policy represents the actual state of asset, because the actual fixed asset revaluation counts the asset by using the market value of the asset, so that the assets are more relevant. This research refers to George Kilirgiotis, (2012). This research aims to examine the factors that push the corporations to revaluate their fixed asset.The populations of this study are non–financial companies listed in Indonesia Stock Exchange (IDX) 2015. The sampling method used is the method of probability sampling technique using random sampling. Total sample of 199 companies are used in analyzing the data. Data are analyzed using multiple regression analysis.The result of this research shows that leverage, firm size, and cash flow operation have positive effect towards fixed asset revaluation, but the result also finds a negative effect between the instensity of fixed asset towards fixed asset revaluation. This research is expected to give information for the financial statement users related to the factors that influence corporations to revaluate their fixed asset.